2015
DOI: 10.1055/s-0035-1544862
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoembryonic antigen (CEA)-related cell adhesion molecules are co-expressed in the human lung and their expression can be modulated in bronchial epithelial cells by non-typable Haemophilus influenzae, Moraxella catarrhalis, TLR3, and type I and II interferons

Abstract: Background: The carcinoembryonic antigen (CEA)-related cell adhesion molecules CEACAM1 (BGP, CD66a), CEACAM5 (CEA, CD66e) and CEACAM6 (NCA, CD66c) are expressed in human lung. They play a role in innate and adaptive immunity and are targets for various bacterial and viral adhesins. Two pathogens that colonize the normally sterile lower respiratory tract in patients with chronic obstructive pulmonary disease (COPD) are non-typable Haemophilus influenzae (NTHI) and Moraxella catarrhalis. Both pathogens bind to C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 19 publications
0
25
1
Order By: Relevance
“…Furthermore, increased expression of TLR2 and CD14 has been reported on CD8 1 T cells in chronic obstructive pulmonary disease (30,31), and in whole sputum in noneosinophilic asthma, associated with increased sputum endotoxin (32). Thus, upregulation in severe neutrophilic asthma of such innate pathogen receptors on T cells, together with other components of the NF-kB signaling pathway and epithelial upregulation of CEACAM5 (a receptor exploited by airway pathogens, including H. influenzae [18]), constitutes a signature suggestive of bacterial infection driving the inflammation of the airways in these individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, increased expression of TLR2 and CD14 has been reported on CD8 1 T cells in chronic obstructive pulmonary disease (30,31), and in whole sputum in noneosinophilic asthma, associated with increased sputum endotoxin (32). Thus, upregulation in severe neutrophilic asthma of such innate pathogen receptors on T cells, together with other components of the NF-kB signaling pathway and epithelial upregulation of CEACAM5 (a receptor exploited by airway pathogens, including H. influenzae [18]), constitutes a signature suggestive of bacterial infection driving the inflammation of the airways in these individuals.…”
Section: Discussionmentioning
confidence: 99%
“…We recently demonstrated that CEACAM5 is also expressed in human airways (20). However, despite the fact that M. catarrhalis also binds to CEACAM5 (4,16), the putative hCEACAM5 dependency for epithelial colonization of CEACAM-binding pathogens in airway epithelium has not yet been investigated.…”
mentioning
confidence: 99%
“…Both can bind to CEACAM1 and induce bacterial adherence and internalization in bronchial epithelial cells, triggering the development of AECOPD. A recent study showed that M. catarrhalis and S. pneumonia per se can increase CEACAM1 mRNA level in normal human bronchial epithelial cells [64].…”
Section: Roles Of Ceacam1 In Copdmentioning
confidence: 99%